Self-employment Intention and Behavior: An Investigation of Determinants and the Moderating Role of Intrinsic Motivation - Waqas, Umair; Umair , Sonia; Al Shamsi, Ibrahim Rashid; Kamran, Hyder; Bystrov , Ilya (Jordan Journal of Business Administration, 2025)
The main purpose of the present study is to examine the determinants of self-employment intention and investigate the moderating role of intrinsic motivation in the effect of self-employment intention on self-employment behavior by using the theory of planned behavior. A questionnaire survey was conducted among 350 public-and private-university students from Lahore, Pakistan. Data was analyzed using SmartPLS. The findings indicate that students’ attitudes, social norms, and perceived behavioral control have strong direct impacts on self-employment intention. Students’ behavior is directly affected by their intention for self-employment and is moderated by intrinsic motivation such that a positive relationship is stronger when intrinsic motivation is higher. There is a dire need to establish a linkage between higher education institutes, industry, and government to boost entrepreneurial activities, as related policies can contribute to the local market and economy of Pakistan. Training and educational programs related to self-employment are needed to be designed so that they can influence the attitude and intrinsic motivation of youngsters. Future studies can take cultural and socio-economic factors into account, as well as the role of extrinsic motivation to get a deeper insight into this concept.